Capilarization Game Foster Childrens’s Cognitive and Language Abilities - Dewi Fitriyatus Sholihah; Bachtiar Syaiful Bachri; Miftakhul Jannah (IJORER : International Journal of Recent Educational Research, 2022)
The purpose of the study was to analyze effect of capillary games foster children’s cognitive and language abilities. The research was conducted using a quasi-experimental design with a quantitative approach. The experimental design used was a nonequivalent control group design. The research study was situated in an Indonesian early childhood education institution with a total of 30 children in the experimental group and 30 children in the control group. The data analysis technique in this study uses parametric statistics independent t test. The results showed that (1) there was an effect of capillary game foster children’s cognitiveve abilities, statistically the value of t = -4.382 with a significant level of p = 0.000 less than 5%; (2) there is an effect of the capillary game on childrens’s language abilities, statistically the value of t = -4.617 with a significant level of 0.000 less than 5%. Based on the results of the research and discussion, it can be concluded that cappilarry games foster childrens’s cognitive and language abilities in an Indonesian early childhood education institution.Through from cappilarry games makes the childrens was recognice many color so the cognitive abilities can be foster. Another ability, cappilarry games make the childrens fluent to be telling stories so the language abilities can be foster. The practical implication in this research is that capillary games can be the foster children’s cognitive and language abilities.